Interferon-γ Restricts Toxoplasma gondii Development in Murine Skeletal Muscle Cells via Nitric Oxide Production and Immunity-Related GTPases - Takács, Anna C. (Public Library of Science, 2012)
The apicomplexan parasite Toxoplasma gondii is regularly transmitted to humans via the ingestion of contaminated meat products from chronically infected livestock. This route of transmission requires intracellular development and long-term survival of the parasite within muscle tissue. In this study, we determined the cell-autonomous immunity of mature primary embryonic or C2C12 skeletal muscle cells (SkMCs) to infection with T. gondii. Non-activated SkMCs and control fibroblasts sustained parasite replication; however, interferon (IFN)-γ significantly inhibited parasite growth in SkMCs but not in fibroblasts. Intracellular parasite replication was diminished by IFN-γ whereas host cell invasion was not affected. Tumor necrosis factor (TNF) did not further increase the IFN-γ-triggered host defense of SkMCs against Toxoplasma. Remarkably, IFN-γ alone or in combination with TNF decreased the high level of T. gondii bradyzoite formation being observed in non-activated SkMCs. Stimulation of SkMCs with IFN-γ strongly triggered expression of inducible nitric oxide synthase (iNOS) transcripts, and induced significantly higher levels of nitric oxide (NO) in SkMCs than in fibroblasts. Consequently, pharmacological inhibition of iNOS partially abrogated the IFN-γ-induced toxoplasmacidal activity of SkMCs. In addition, SkMCs strongly up-regulated immunity-regulated GTPases (IRGs) following stimulation with IFN-γ. IRGs accumulated on Toxoplasma-containing vacuoles in SkMCs in a parasite strain-dependent manner. Subsequent vacuole disruption and signs of degenerating parasites were regularly recognized in IFN-γ-treated SkMCs infected with type II parasites. Together, murine SkMCs exert potent toxoplasmacidal activity after stimulation with IFN-γ and have to be considered active participants in the local immune response against Toxoplasma in skeletal muscle.